2018
DOI: 10.3762/bjoc.14.170
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of π–extended “earring” subporphyrins

Abstract: A π-extended “earring” subporphyrin 3 was synthesized from β,β′-diiodosubporphyrin and diboryltripyrrane via a Suzuki–Miyaura coupling and following oxidation. Its Pd complex 3Pd was also synthesized and both of the compounds were fully characterized by 1H NMR, MS and X-ray single crystal diffraction. The 1H NMR spectra and single crystal structures revealed that aromatic ring current did not extend to the “ear” in both of the two compounds. Their UV–vis/NIR spectra were recorded and the absorption of both com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Next to the nickel­(II) ion in the regular porphyrin portion of the molecule, a second metal ion can be accommodated in the N 3 C coordination environment of the carbaporphyrin-type “ear”. A subporphyrin variety and heterole-fused earring porphyrins have also become known. , …”
Section: Metalloporphyrinoids Containing Nonpyrrolic Building Blocksmentioning
confidence: 99%
See 1 more Smart Citation
“…Next to the nickel­(II) ion in the regular porphyrin portion of the molecule, a second metal ion can be accommodated in the N 3 C coordination environment of the carbaporphyrin-type “ear”. A subporphyrin variety and heterole-fused earring porphyrins have also become known. , …”
Section: Metalloporphyrinoids Containing Nonpyrrolic Building Blocksmentioning
confidence: 99%
“…A subporphyrin variety and heterolefused earring porphyrins have also become known. 462,463 The X-ray structure of 138NiPd shows the assembly to be a smoothly curved plane, whereby the porphyrin half is more displaced from planarity than the Pd-ear. Since the structure of "free-base" ligand 138Ni is also known, 462 it could be shown that the insertion of Pd(II) caused an increased curvature of the assembly 138NiPd.…”
Section: Metalloporphyrinoids With N 2 C 2 -Coordination Spheresmentioning
confidence: 99%
“…“Earring” porphyrins C36.1 , C36.2 , and C36.6 , containing tripyrrin loops fused to the macrocyclic core, were developed by Song and Kim et al ( Chart 36 ). 733 , 734 The synthetic strategy, based on Suzuki–Miyaura coupling, was subsequently extended to develop the heterole-fused derivatives C36.3 – 5 . 735 These porphyrinoids possess multiple coordination cavities and can accommodate two or three metal ions per molecule, with meso carbons acting as organometallic donors in the earring loops.…”
Section: Macrocyclic Systemsmentioning
confidence: 99%
“…The carbatetraphyrinic environmenth as been createds tarting from diiodotriphyrin(1.1.1) 4b that in the Suzuki-Miyaura couplingw ith 21 gave 22 in 15 %. [16] The structural construction of 22 opens ap ossibility for observing changes in delocalization that can eventually be extendedt oa ntiaromatic 24p electrons (Scheme 5, green). The spectroscopic properties have shown af ormation of structure where the triphyrin(1.1.1) delocalization dominates and the optical response is very subtly changed by the additional fragment of molecule but there was no fluorescencer ecordedf or 22.T he most probable factor is af lexibility and limited planarity of the final molecule.…”
Section: Triphyrin-tetraphyrin Hybridmentioning
confidence: 99%
“…A specific merging of two structural motifs has been realized by Song and co‐workers (Scheme ). The carbatetraphyrinic environment has been created starting from diiodotriphyrin(1.1.1) 4 b that in the Suzuki–Miyaura coupling with 21 gave 22 in 15 % . The structural construction of 22 opens a possibility for observing changes in delocalization that can eventually be extended to antiaromatic 24π electrons (Scheme , green ).…”
Section: In‐cavity Coordinationmentioning
confidence: 99%